Effect of oxytocin nasal spray pretreatment on postoperative acute stress disorder in patients with accidental traumatic fracture: a single-centre prospective randomised controlled clinical trial study protocol - Ling Ren; Qingqing Huang; Hengdi Zhang; Jingzheng Zeng; Yi Wen; Haifeng Shu; Gu Gong (BMJ Open)
Introduction Patients undergoing surgical procedures are often prone to developing acute stress disorder (ASD) postoperatively. Presently, oxytocin nasal spray has shown significant potential in the treatment of stress-related neuropsychiatric diseases. However, there are few reports on the use of oxytocin nasal spray in postoperative ASD, a condition that can potentially develop into a high-risk factor for post-traumatic stress disorder. This study aims to investigate the effect of pretreatment with oxytocin nasal spray on postoperative ASD in patients with accidental trauma and fracture to provide new clinical insights for the prevention of postoperative ASD.Methods and analysis This study is a single-centre, double-blind, randomised controlled clinical trial. The trial aims to recruit 328 patients with accidental traumatic fractures who underwent surgical treatment. Participants will be randomly categorised into two groups: a control group (0.9% normal saline nasal spray, 1 mL) and an oxytocin group (oxytocin nasal spray, 1 mL/40 IU) at a ratio of 1:1 using the random number table method. The primary outcome is the incidence of ASD on postoperative days 1–3. Secondary outcomes include patient resilience, anxiety, depression and pain scores on postoperative days 1–3. The exploratory results include the concentrations of stress response indicators such as malondialdehyde, cortisol and superoxide dismutase in the saliva before the first intervention and on days 1–3 after surgery.Ethics and dissemination The trial was approved by the clinical research ethics committee of the General Hospital of the Western Theater Command (identifier: 2024EC3-ky014). The findings of this trial will be disseminated in a peer-reviewed journal and in national or international paediatric research to guide future practice.Trial registration number ChiCTR2400082612.